Transforming Kolkata a partnership for a more sustainable, inclusive, and resilient city. - Pokhrel, Neeta
This publication summarizes the outcomes to date and explores the views of stakeholders in the 2 decades of partnership between ADB and the Kolkata Municipal Corporation in India.